One‐year clinical outcome of biodegradable polymer sirolimus‐eluting stent in patients presenting with acute myocardial infarction: Insight from the ULISSE registry. Issue 7 (29th April 2019) - Moscarella, Elisabetta; Ielasi, Alfonso; Beneduce, Alessandro; Ferrante, Giuseppe; Pivato, Andrea Carlo; Chiarito, Mauro; Cappelletti, Alberto; Perfetti, Giulia; Magni, Valeria; Prati, Eugenio; Falcone, Stefania; Pierri, Adele; et al.
Abstract: Background: The ULISSE registry has demonstrated the real‐world performance of the Ultimaster biodegradable polymer sirolimus‐eluting stent (BP‐SES) in a large cohort of patients undergoing percutaneous coronary intervention, including a large proportion of patients presenting with acute myocardial infarction (AMI). Methods: We performed a subgroup analysis of the ULISSE registry in AMI patients and compared the outcomes of this vulnerable cohort with that of patients presenting without AMI (non‐AMI). The primary end point was the incidence of 1‐year target lesion failure (TLF), a composite of cardiac death, target vessel myocardial infarction (TV‐MI), and clinically indicated target lesion revascularization (TLR). Results: Of 1, 660 patients included in the ULISSE registry, 381(23%) presented with AMI, 207(54.3%) non‐ST elevation myocardial infarction, and 174(45.7%) ST‐elevation myocardial infarction. Compared with non‐AMI patients, those with AMI were more frequently female and smokers, with lower left ventricular ejection fraction (LVEF) and chronic kidney disease requiring dialysis. At 1 year, TLF rate was significantly higher in AMI than non‐AMI patients (7.9 vs. 4.1%; HR 1.98, CI 95% 1.22–3.23; p = .005) driven by higher rate of cardiac death (4.0 vs. 1.1%; HR 3.59, CI 95% 1.64–7.88; p = .01) and TV‐MI (2.8 vs 0.9%; HR 2.99, CI 95% 1.22–7.37; p = .01), without differences in TLR rate (4.3 vs. 2.9%, HR 0.66, CI95% 0.35–1.25; p = .2). At multivariate Cox regression analysis, eGFR <40 mL/min (HR: 2.868) and LVEF <40% (HR: 2.394) were the only independent predictors of TLF. Conclusions: In AMI patients, Ultimaster BP‐SES implantation was associated with higher rate of TLF and definite stent thrombosis compared with non‐AMI patients. The high incidence of adverse events was mainly driven by the unfavorable baseline risk profile.